'Dominus dixit': principles of exegetical theology applied in two loci of Peter Martyr Vermigli's I Corinthians commentary. Issue 1 (5th February 2014) - Rester, Todd M.
Abstract : The article reviews Peter Martyr Vermigli's hermeneutical principles outlined in his I Corinthians commentary and examines Martyr's understanding of the authority of Scripture and the Church as contrasted with a Roman Catholic interlocutor, Stanislaus Hosius; it also analyzes two test cases in Vermigli's loci that demonstrate a constructive and destructive use, respectively, of his hermeneutical principles. The demonstrations evaluate Vermigli's positive statement of the doctrine of justification and his polemical engagement with the doctrine of purgatory.